Effects of Flavonoid Fractions from Calendula officinalis Flowers in Parent and Tamoxifen Resistant T47D Human Breast Cancer Cells: Effects of flavonoids in human breast cancer cells - Ostad, Seyed Naser; Monsef-Esfahani, Hamid Reza; Taheri, Samira; Azizi, Ebrahim; Faramarzi, Mohammad Ali (Iranian Journal of Pharmaceutical Sciences, 2005)
Three major flavonoid fractions were separated from a methanol extract of Calendula officinalis flowers by preparative TLC. These fractions were evaluated for the inhibition of parent and tamoxifen resistant T47D human breast cancer cells. We also examined the effect of quercetin and isorhamnetin on the growth of parent and resistant T47D cells in the presence and absence of tamoxifen. It was found that quercetin increased cell proliferation of the resistant T47D cells at the presence of tamoxifen but no effect was detected by using quercitin alone. The fractions isolated from Calendula officinalis did not show any inhibitory effects on the cells.Isorhamnetin did not have any proliferative or anti-proliferative activity on the both cell lines.